Desarrollo de un sistema informático para el departamento de Terapia de Lenguaje del Centro de Educación Especial “Nuestra Señora del Carmen” utilizando tecnología .NET y bases de datos en el cantón Urdaneta provincia de Los Ríos - Gaibor Silva, Karla Leonor (2014)
The proposed thesis project as "Developing a computer system for the area of Speech Therapy Special Education Center" Our Lady of Carmen "using NET technology and databases in Urdaneta Canton province of Los Rios," was developed technological tool with visual 2010 which has been downloaded and installed to proceed with programming. The assurances within the system is a very important point is why when entering the system especially for user authentication that is, a LOGIN, thus allowing the system input do only authorized persons if you enter as Guest only you can consult while if you can login as Administrator to do the following as a new, query, modify, delete. The developed system esta estructurada chapters: The first chapter addresses the objectives as well as the overall objective and specific. In Chapter II research is supported as a reference framework is the background if some other link has been made to similar projects being developed in the theoretical framework with the knowledge of the use of technological tools, the hypothesis to be defend during the project such as general and specific hypotheses. In Chapter III the results of the research, each question that parents of families was done in this case are 10 questions with their analysis and interpretation of each question is displayed, the calculations were performed with the use of the Excel program . In chapter IV are the conclusions why the creation of the system in which it made in view that the Department of Speech Therapy does not have a system (software) entering information in the department of speech therapy would currently done manually as well as the system users have accounts of making the information is handled properly. In Chapter V the recommendations that should enable the person to manipulate the system to be updated databases detailing. A proposal to implement a plan for recording information using a system in the area of therapy Language Special Education Center "Our Lady of Carmen" Urdaneta Canton province of Los Rios is described in Chapter VI, which is the screen shots of the system is recording, background and evidence within the MDI reports of each of the forms as information recording history and evidence is found, it is displayed the switch user screen and whose exceptions are querying each form but not data entry. Chapter VII of the direction the literature is that it is consulted for this information computer system. Finally there are the Annexes as Annex 1 is the survey form with 10 questions to parents was conducted in Annex 2 are the questions asked to the people working in the department of speech therapy in the Annex 3 contains a glossary of terms with definitions of each word, in Annex 4 are the technical Manual is both the static model with each of the diagrams such as the identification of actors, use case diagram, dictionary use cases within the dynamic model. The sequence diagram and data dictionary.